2013
DOI: 10.5194/bg-10-6215-2013
|View full text |Cite
|
Sign up to set email alerts
|

Export of <sup>134</sup> Cs and <sup>137</sup> Cs in the Fukushima river systems at heavy rains by Typhoon Roke in September 2011

Abstract: Abstract. At stations on the Natsui River and the Same River in Fukushima Prefecture, Japan, effects of a heavy rain event on radiocesium export were studied after Typhoon Roke during 21-22 September 2011, six months after the Fukushima Dai-ichi Nuclear Power Plant accident. Radioactivity of 134 Cs and 137 Cs in river waters was 0.009-0.098 Bq L −1 in normal flow conditions during July-September 2011, but it increased to 0.85 Bq L −1 in high flow conditions because of heavy rains occurring with the typhoon. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(71 citation statements)
references
References 24 publications
5
65
1
Order By: Relevance
“…In the Kharkiv region of Ukraine, the mean annual precipitation is 460 mm yr 1 (Nazarok et al, 2014); in Odessa it is < 500 mm yr −1 (Svetlitchnyi, 2009) compared to 1420 mm yr −1 for the Fukushima region. In Ukraine, the region within a 100 km radius from Chernobyl has a rainfall erosivity that ranges from 830 to 1250 MJ mm ha −1 h −1 yr −1 (Larionov, 1993).…”
Section: Implications For Radiocesium Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Kharkiv region of Ukraine, the mean annual precipitation is 460 mm yr 1 (Nazarok et al, 2014); in Odessa it is < 500 mm yr −1 (Svetlitchnyi, 2009) compared to 1420 mm yr −1 for the Fukushima region. In Ukraine, the region within a 100 km radius from Chernobyl has a rainfall erosivity that ranges from 830 to 1250 MJ mm ha −1 h −1 yr −1 (Larionov, 1993).…”
Section: Implications For Radiocesium Dynamicsmentioning
confidence: 99%
“…In fact, the majority of soil erosion and concomitant radiocesium migration was reported to coincide with extreme rainfall events (Mouri et al, 2014;Nagao et al, 2013;Onishi et al, 2014). For example, reported that most sediment-bound radiocesium migration occurs in flood events that may only occur 1 to 2 times per year.…”
Section: Introductionmentioning
confidence: 99%
“…The possible sources of radioactive Cs to these coastal areas (T1, T12, T18 and Onahama in Fig. 2) have been discussed such as the continuous leakage from the port of FNPP site (Kanda, 2013), and river discharge (Nagao et al, 2013;Kakehi et al, 2016), after the peak duration of heavily contaminated water release during the end of March from May 2011 . Continuous monitoring should be conducted to clarify how these continuous sources affect the concentration level of radioactive Cs in the coastal area around the FNPP site.…”
Section: Fukushima-derived Radioactive Cesium In Near Coastal Area Ofmentioning
confidence: 99%
“…The second long-term source of 137 Cs to the ocean is river-borne waters and sediments (Nagao et al, 2013, Chartin et al, 2013. Nagao et al (2013) found that up to half of the annual Cs flux from the Japanese rivers is from heavy rain events.…”
Section: Cycling Of Cesium In the Oceanmentioning
confidence: 99%
“…Nagao et al (2013) found that up to half of the annual Cs flux from the Japanese rivers is from heavy rain events. Because Cs is largely insoluble in freshwater, its transport and delivery via rivers is much more tied to the Cs on right.…”
Section: Cycling Of Cesium In the Oceanmentioning
confidence: 99%